Subwavelength Index Engineering for SOI Waveguides - Halir, Robert; Luque-González, José Manuel; Wang, S.; Sarmiento-Merenguel, Jose Darío; Sánchez-Postigo, Alejandro; Wanguemert-Pérez, Juan Gonzalo; Cheben, Pavel; Schmid, Jens H.; Xu, Dan-Xia; Janz, Siegfried; Lapointe, J.; Molina-Fernández, Íñigo; et al. (My University, 2016)
Photonic structures with a sub-wavelength pitch, small enough to suppress diffraction, can behave as equivalent homogenous materials that can be engineered to exhibit a specific refractive index and dispersion. Here we discuss the design of a variety of integrated photonic devices, ranging from grating couplers to multimode interference couplers, for which the use of sub-wavelength structures enables unique characteristics. We will place special emphasis on the design and experimental demonstration of multi-mode interference couplers with an unprecedented bandwidth beyond 200nm at telecom wavelengths.
Keywords: Optica integrada; Integrated Optics; Sub-wavelength structures